2018
DOI: 10.3389/fphar.2018.01003
|View full text |Cite
|
Sign up to set email alerts
|

Did the New Italian Law on Mandatory Vaccines Affect Adverse Event Following Immunization’s Reporting? A Pharmacovigilance Study in Southern Italy

Abstract: Despite the well-recognized role of vaccines, coverage is far from optimal especially in children, representing a growing concern also in Italy. In order to reverse this emergency, the Italian Ministry approved in July 2017 the Law 119/2017, which renders mandatory and free of charge 10 vaccinations for patients aged 0–16. We aim to investigate the effects of the new Law 119/2017 on the reporting of adverse events following immunization related to mandatory vaccines into the Italian Pharmacovigilance database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Whilst men have an increased risk of gout and hyperuricemia and, therefore, are more prone to be treated with allopurinol, we found that ADRs, especially serious cutaneous ADRs, were more common in women. This is not surprising because females seem to be more likely at risk to experience ADRs due to sex-specific differences in the pharmacokinetics and pharmacodynamics of drugs [34][35][36][37]. Furthermore, literature data confirm that both SJS and TEN could occur at any age, but appear to be more prevalent in adults, with a slight predominance in women [38,39].…”
Section: Overall Resultsmentioning
confidence: 94%
“…Whilst men have an increased risk of gout and hyperuricemia and, therefore, are more prone to be treated with allopurinol, we found that ADRs, especially serious cutaneous ADRs, were more common in women. This is not surprising because females seem to be more likely at risk to experience ADRs due to sex-specific differences in the pharmacokinetics and pharmacodynamics of drugs [34][35][36][37]. Furthermore, literature data confirm that both SJS and TEN could occur at any age, but appear to be more prevalent in adults, with a slight predominance in women [38,39].…”
Section: Overall Resultsmentioning
confidence: 94%
“…Furthermore, hypercholesterolaemia seems to be more common in women, particularly after menopause, which has been shown to be associated with an increase in total and LDL-cholesterol [32][33][34][35][36][37][38][39]. Lastly, it should be noted that, independently by drug classes, women are more susceptible to experience ADRs due to hormonal factors, as well as changes in pharmacokinetics [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, vaccination safety was confirmed by the evidence that the majority of ADE reports were not associated to vaccines, nor increased risk of hospitalization due to AEFI occurrence was observed among sexes. Although vaccines represent one of the most frequent cause of ADE in specific subgroups, such as children, their safety was confirmed by several observational studies and by health care authorities: adverse events following immunization are mostly non-serious and rarely cause ED visits and hospitalization [15].…”
Section: Discussionmentioning
confidence: 96%